Structure and Properties of Arc Ion Plating Deposited AlCrSiN Coatings Controlled by Pulsed Bias Voltage - Rui Zhang; Yanmei Liu; Chongyang Wang; Fengting Cao; Qixiang Fan; Tiegang Wang (Metals, 2023)
AlCrSiN coatings are promising protective candidates for cutting and forming tools. During the coating deposition process, the microstructure and properties of the coatings were dramatically affected by bias voltages. To further optimize and enhance the AlCrSiN coating, a series of coatings were deposited at different pulse bias voltages using arc ion plating technology. By virtue of scanning electron microscopy, X-ray diffraction, scratch method, OCP, EIS, and other analytical methods, the effects of the pulse bias voltage on the crystal structure, microstructure, and mechanical, tribological, and electrochemical properties of the AlCrSiN coatings were analyzed. The study revealed that the pulse bias voltage exerted a slight influence on the aluminum and nitrogen content of the coatings. As the pulse bias voltage increased, the hardness, critical load, and tribological performance of the AlCrSiN coatings first increased gradually, and then were impaired slightly. When the pulse bias voltage was −100 V, the resulting AlCrSiN coating exhibited the densest structure, the highest hardness, the strongest adhesion, and the best wear resistance. In this case, the coating hardness and critical load reached 2668 HV and 72.7 N, respectively. The friction coefficient and wear rate were 0.35 and 1.02 × 10−3 μm3/N·μm, respectively. Simultaneously, the AlCrSiN coating demonstrated exceptional corrosion resistance in 3.5 wt.% NaCl solutions, surpassing uncoated 304 steel by 3~4 times.